Preparation of Water Erosion Risk Map for AL-Abrash River Basin Soil in Tartous Using CORINE Model and GIS - بركات, منى علي; العبد , محمد; حسن, عزالدين; جوهره, علي (Latakia University Journal -Biological Sciences Series, 2020)
This study aimed to prepare a Risk map of water erosion for AL-A brash River Basin using CORINE model and geographic information system (GIS). Corine model depend on calculating all factor that affect water erosion such as soil erodibility, erosivity, slope and land cover parameters. Soil erodibility was evaluated through estimating (soil texture, soil depth, and stoness percentage), slop classes were generated from digital elevation model (Dem), rainfall erosivity index was calculated by using Fournier Index (FI) and (BGI: Bagnouls-Gaussen Index), and the type of land cover was classified intotwo classes by the degree of protection provided the soil. Then the final risk map was prepared through multiplication of these four factors for the entire study area.The result showed that,4.81% of studied area has a high erosion risk, 22.15% has a moderate risk, and 73.04% has low risk. The regions of high erosion risk were located in the east northern parts of the study area.